Phelps Stokes commission, Africa - Vischer, Hanns; Stokes, Anson Phelps; Great Britain Colonial Office; National Archives (Great Britain); Adam Matthew Digital (Adam Matthew Digital, 1923)
Colonial Office file containing memoranda and correspondence relating to arrangements for the appointment and visit of an education commission to East Africa, funded by the Phelps-Stokes Fund. Includes: Report by Major Vischer on his journey to the East African dependencies with the Phelps-Stokes Education Commission and his visits to Bechuanaland and Basutoland (1924)